One new species and one new record of family Photidae Boeck, 1871 (Amphipoda: Senticaudata) from Gujarat, India - Thacker, Dimple; Myers, Alan A.; Trivedi, Jigneshkumar N. (Zootaxa, 2025)
The present study was conducted based on the amphipod specimens collected from the Veraval coast of Gujarat state, India. From the collection, 2 species of family Photidae Boeck, 1871 were identified: Audulla sindhu sp. nov. and Latigammaropsis photisimilis (Ruffo, 1969). Audulla sindhu sp. nov. can be differentiated from its only congener Audulla chelifera Chevreux, 1901 by having gnathopod 2 propodus comparatively longer and slender and presence of uropod 1 inter-ramus spur. Another species Latigammaropsis photisimilis (Ruffo, 1969) is first time reported from India in the study which was only reported from Red Sea (Ruffo, 1969) till now.